2019
DOI: 10.2174/2215083804666181002095249
|View full text |Cite
|
Sign up to set email alerts
|

Aristotelia chilensis (Mol.) Stuntz: A Natural Source of Bioactive Compounds

Abstract: Aristotelia chilensis (Mol.) Stuntz, commonly called “maqui” is a native tree of Chile considered sacred for the Mapuche people. The fruits are sweet blackberries with a high concentration of polyphenols which stain the hands and mouth when eaten. The Mapuche people use it for creating "chicha" an alcoholic beverage, while leaves are used to treat infected wounds, inflammation and ulcers. In this review, we will give an overview of the pharmacology reported for the plant and molecules isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Compounds 17, 18 and 20 showed a deprotonated molecular ion of monoglycosides. Peaks 17 and 18 should be quercetin-3-Ohexosides isomers, which would agree with quercetin-3-O-galactoside (17) and quercetin-3-O-glucoside (18) [36], and quercetin-3-O-pentoside (20) (Table 2). Peak 11 presented a deprotonated molecular ion at m/z 615 with a loss of 152 amu after the MS fragmentation event (galloyl radical), and other ions at m/z 301 (deprotonated quercetin), which indicated that this compound was quercetin-3-O-(galloyl) hexoside.…”
Section: Ellagitanninsmentioning
confidence: 66%
See 3 more Smart Citations
“…Compounds 17, 18 and 20 showed a deprotonated molecular ion of monoglycosides. Peaks 17 and 18 should be quercetin-3-Ohexosides isomers, which would agree with quercetin-3-O-galactoside (17) and quercetin-3-O-glucoside (18) [36], and quercetin-3-O-pentoside (20) (Table 2). Peak 11 presented a deprotonated molecular ion at m/z 615 with a loss of 152 amu after the MS fragmentation event (galloyl radical), and other ions at m/z 301 (deprotonated quercetin), which indicated that this compound was quercetin-3-O-(galloyl) hexoside.…”
Section: Ellagitanninsmentioning
confidence: 66%
“…According to the results of HPLC-DAD-ESI-MS n , the expression of phenolics compounds was more related to the type of leaf than to the season of the year. It is well-known that phenols are a distinctive feature of A. chilensis , and some of its nutritional and pharmacological effects can be attributed to their presence in the plant [ 17 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations